Kompetensi Wanita Tani dan Hubungannya dengan Pengambilan Keputusan pada Usahatani Jagung Manis di Lahan Gambut Kecamatan Rasau Jaya - Pratiwi, Audi; Dewi Kurniati, Dewi Kurniati; Suyatno, Adi (Universitas Galuh, 2024)
Farmers have long used peatlands, especially shallow peat, as agricultural areas. Sweet corn is the second vital commodity after paddy or rice in Indonesia which can grow on peatlands. Rasau Jaya District is one of the areas that produces the largest sweet corn in Kubu Raya Regency, but the amount of production tends to be unstable. Farmers are required to be able to make the right decisions regarding the management of their farming business because it can affect the production of the farming business. Decision making on sweet corn farming also involves women farmers. Even so, the competence of women farmers in making farming decisions is still often doubted. This research aims to: 1) Identify the level of competence of women farmers and decision making, 2) Analyze the relationship between women farmers' competence and decision making in sweet corn farming on peatlands, Rasau Jaya District. This research uses quantitative methods. The analysis used is interval class analysis via Microsoft Excel 2010 and Spearman rank correlation analysis via the SPSS 25.0 for Windows application. Primary and secondary data were collected through interviews, questionnaires and observations. The results of the research show that the level of competency of women farmers in sweet corn farming in the peatlands of Rasau Jaya District is included in the medium category. Then, the competence of women farmers has a significant relationship with decision making in sweet corn farming on peatlands, Rasau Jaya District.